2000
DOI: 10.1136/jcp.53.12.917
|View full text |Cite
|
Sign up to set email alerts
|

Fetal macrosomia related to maternal poorly controlled type 1 diabetes strongly impairs serum lipoprotein concentrations and composition

Abstract: Aims-To determine the eVects of fetal macrosomia related to maternal type 1 diabetes on the lipid transport system. Methods-Serum lipoprotein concentrations and composition and lecithin:cholesterol acyltransferase (LCAT) activity were investigated in macrosomic newborns (mean birth weight, 4650 g; SEM, 90) and their mothers with poorly controlled type 1 diabetes, in appropriate for gestational age newborns (mean birth weight, 3616 g; SEM, 68) and their mothers with well controlled type 1 diabetes, and macrosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 39 publications
2
39
2
3
Order By: Relevance
“…Studies of macrosomic newborns of diabetic or obese mothers have shown higher serum lipids and apolipoproteins compared with AGA newborns of healthy mothers (8,9). These data suggest that the synthesis of fat and protein might be increased in these fetuses (8,9). However, in macrosomic newborns of nondiabetic and nonobese mothers, serum lipid and apolipoprotein values did not differ significantly from those in AGA newborns (8,11).…”
Section: Results -The Mean (ϯSd) Anthropometric Indexes Of the 37contrasting
confidence: 41%
See 3 more Smart Citations
“…Studies of macrosomic newborns of diabetic or obese mothers have shown higher serum lipids and apolipoproteins compared with AGA newborns of healthy mothers (8,9). These data suggest that the synthesis of fat and protein might be increased in these fetuses (8,9). However, in macrosomic newborns of nondiabetic and nonobese mothers, serum lipid and apolipoprotein values did not differ significantly from those in AGA newborns (8,11).…”
Section: Results -The Mean (ϯSd) Anthropometric Indexes Of the 37contrasting
confidence: 41%
“…This difference became greater with increasing birth weight. Studies of macrosomic newborns of diabetic or obese mothers have shown higher serum lipids and apolipoproteins compared with AGA newborns of healthy mothers (8,9). These data suggest that the synthesis of fat and protein might be increased in these fetuses (8,9).…”
Section: Results -The Mean (ϯSd) Anthropometric Indexes Of the 37mentioning
confidence: 68%
See 2 more Smart Citations
“…GDM patients with macrosomic fetuses have been associated with high triacylglycerol, VLDL, and low HDL levels (78). Moreover, macrosomic newborns of poorly controlled GDM patients have higher lipid and lipoprotein concentrations than those found in control subjects (79).…”
Section: Amino Acids and Protein Metabolism Inmentioning
confidence: 99%